Efficacy and safety of pharmacological interventions for pruritus in primary biliary cholangitis: A systematic review and meta-analysis - Xu, Chenyi; Yue, Rensong; Lv, Xuelian; Wang, Shengnan; Du, Mengmeng (Frontiers in Pharmacology, 2022)
Pruritus is a common complication in patients with primary biliary cholangitis (PBC). The pathogenesis is not clear, and also the precise therapeutic measures remain alluring. In order to systematically evaluate the efficacy and safety of drug interventions in the treatment of pruritus associated with PBC, this systemic review and meta-analysis was conducted. The randomized controlled trials (RCTs) on drug interventions in the treatment of pruritus associated with primary cholangitis were searched in the electronic databases of PubMed, EMBASE, Cochrane Library, Web of Science, and ClinicalTrials.gov. Two researchers independently screened the literature, extracted and integrated the data, and assessed the bias risk of the selected literature, according to the Cochrane handbook. Finally, the STATA 15.0 software was used for the meta-analysis. A total of 23 RCTs involving 2194 patients were studied, that included 12 pharmacological interventions. In terms of itching relief, compared with placebo, UDCA, methotrexate and GSK2330672 had a definite effect in improving pruritus (pruritus remission rate before and after treatment, P < 0.05). In terms of serum indexes, compared with placebo group, UDCA, OCA, rifampicin, cyclosporine, NGM282, seladelpar and colchicine may improve blood alkaline phosphate (ALP) (P<0.05), but only rifampicin showed low heterogeneity. UDCA, bezafibrate, OCA, rifampicin, NGM282 and others may improve blood γ-glutamyl transpeptidase (γ-GGT) (P<0.05), but due to the high heterogeneity and the limitation of research samples, a clear conclusion cannot be drawn. In terms of adverse events, except high(>15mg/kg/day) and low doses(<13mg/kg/day) of UDCA increased the incidence of adverse events, there were no risk of increasing the incidence of adverse events compared with placebo (P>0.05), and a moderate dose of UDCA (13-15mg/kg/day) and malotilate (1500mg/day) may also help in reducing the incidence of adverse events (P<0.05). Conclusions: UDCA, methotrexate and GSK2330672 may relieve itching in patients with PBC, but there is a lack of robust evidence to support their effect on ALP or γ-GGT. Due to the heterogeneity in the published studies, based on the present review, we cannot explicitly recommend any specific drug for the treatment of PBC-related pruritus. Keywords: primary biliary cholangitis, pruritus, pharmacological interventions, Alkaline phosphate, γ-glutamyl transpeptidase. OSF register number: DOI 10.17605/OSF.IO/2G8YA